Makna Perang Jagaraga dalam Kerangka Sejarah Nasional Sebagai Bentuk Kepribadian Bangsa Indonesia - Ida Ayu Putu Mahyuni (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2023)
In the 19th and 20th centuries, there were a number of battles the Balinese people fought against the Dutch colonial government. Resistance either in the form of war or puputan occurred successively in the royal territories in Bali, starting from the Buleleng war, Jagaraga war, Banjar war, Kusamba war, Badung puputan, Klungkung puputan to Margarana puputan. This paper focuses on the Jagaraga war within the framework of national history which was carried out by the Balinese people under the command or army leaders from among the kings, governors, relatives of the kings, and even among ordinary people, such as Jero Jempiring at the Battle of Jagaraga. From this background, the problems discussed in this paper are: (1) What is the meaning of the link between the paramilitary leader and his followers? (2) What is the meaning of Hindu philosophy in the Jagaraga war? and (3) What is the meaning of the Jagaraga war in the framework of National history?.